Ambidexterity-Based Islamic Boarding School Curriculum Management - Abdullah Abdullah; Ahmad Nadif Sanafiri (LP. Ma'arif Janggan Magetan, 2024)
This research aims to identify and analyze ambidextrous curriculum management at Nurul Jadid Islamic Education School Jalaluddin Ar-Rumi rigion. To expand the implementation of an ambidextrous curriculum at the Islamic Education School, a qualitative approach and case study methodology are utilized. The research subjects include regional supervisors, administrators, and students involved in curriculum management. Data collection methods involve observation, in-depth interviews, and document analysis related to the curriculum. Thematic analysis is employed to identify patterns and themes relevant to the ambidexterity approach. The findings indicate that Nurul Jadid Islamic Education School Jalaluddin Ar-Rumi rigion has successfully integrated traditional values with contemporary curriculum components through an ambidextrous approach. This approach has proven effective in enhancing students' adaptation to technological advancements and modern knowledge while maintaining the Islamic Education Schools identity. It is hoped that this research will serve as a foundation for further development aimed at improving the relevance and effectiveness of Islamic Education Schools in the face of modern educational changes and advancements.